Changes in neural resting state activity in primary and higher-order motor areas induced by a short sensorimotor intervention based on the Feldenkrais method - Verrel, Julius; Almagor, Eilat; Schumann, Frank; Lindenberger, Ulman; Kühn, Simone (Frontiers in Human Neuroscience, 2015)
We use functional magnetic resonance imaging to investigate short-term neural effects of a brief sensorimotor intervention adapted from the Feldenkrais method, a movement-based learning method. Twenty-one participants (10 men, 19-30 years) took part in the study. Participants were in a supine position in the scanner with extended legs while an experienced Feldenkrais practitioner used a planar board to touch and apply minimal force to different parts of the sole and toes of their left foot under two experimental conditions. In the local condition, the practitioner explored movement within foot and ankle. In the global condition, the practitioner focused on the connection and support from the foot to the rest of the body. Before (baseline) and after each intervention (post-local, post-global), we measured brain activity during intermittent pushing/releasing with the left leg and during resting state. Independent localizer tasks were used to identify regions of interest (ROI). Brain activity during left-foot pushing did not significantly differ between conditions in sensorimotor areas. Resting state activity (regional homogeneity, ReHo) increased from baseline to post-local in medial right motor cortex, and from baseline to post-global in the left supplementary/cingulate motor area. Contrasting post-global to post-local showed higher ReHo in right lateral motor cortex. ROI analyses showed significant increases in ReHo in pushing-related areas from baseline to both post-local and post-global, and this increase tended to be more pronounced post-local. The results of this exploratory study show that a short, non-intrusive sensorimotor intervention can have short-term effects on spontaneous cortical activity in functionally related brain regions. Increased resting state activity in higher-order motor areas supports the hypothesis that the global intervention engages action-related neural processes.